Antiproliferative Potential of Essential Oil from the Leaves of Croton floribundus (Euphorbiaceae) Against Human Metastatic Melanoma Cell Lines - Garcia D.A.; Costa L.P.D.M.; Rosa W.; Ladvocat A.C.C.P.; Dias D.F.; Soares M.G.; Ionta M.; Chagas-Paula D.A.
Melanoma is a cancer type with high lethality, metastatic capacity, and limited therapeutic options. Different essential oils have been reported with antitumoral potential. Thus, the essential oil (EO) of the leaves of C. floribundus was obtained by hydrodistillation and analyzed by GC-MS. The majority of substances annotated were ?-selinene, E-Caryophyllene, and Premnaspirodiene. The cytotoxic activity of EO was evaluated on three melanoma cell lines SKMEL-147, WM-1366, and CHL-1, which are representative of metastatic melanoma with different mutation profiles. The IC50 values found for EO were lower than temozolomide (reference drug) in all melanoma cell lines. In addition, the selectivity of EO was upward when compared to the reference drug. Interestingly, the WM-1366 cell line was the most responsive, and these findings are very promising considering that it has shown high resistance to the plethora of compounds. Thus, the C. floribundus EO is a promising source to drive further studies for the development of new treatments for metastatic melanoma, which is urgently relevant given the resistance of this pathology to current treatments. © 2024 Wiley-VHCA AG, Zurich, Switzerland.
Keywords: CROTON; ESSENTIAL OIL; GC-MS; MELANOMA; METASTASIS